INTEGRASI PSIKOLOGI KELUARGA DAN AJARAN ISLAM DALAM PENYELESAIAN KONFLIK KELUARGA: PENDEKATAN KUALITATIF UNTUK MEWUJUDKAN KELUARGA SAKINAH, MAWADDAH, DAN RAHMAH - Abdurahman (PT. Hasba Edukasi Mandiri, 2025)
Family conflict is an inevitable phenomenon in married life, which can be triggered by various internal and external factors. This study aims to examine how the integration of family psychology approaches and Islamic values can be used to resolve family conflicts. Using a qualitative approach and a case study design, the research collects data through in-depth interviews with couples, parents, as well as family psychology experts and religious figures. The findings indicate that effective family conflict resolution relies not only on psychological approaches but also on Islamic principles such as consultation, justice, patience, and forgiveness. This approach can create a harmonious, sakinah, mawaddah, and rahmah family, capable of managing conflicts wisely and strengthening family resilience.